PENGELOLAAN BADAN USAHA MILIK DESA (BUMDes) DI DESA SUNGAI SERIA KECAMATAN KETUNGAU HULU KABUPATEN SINTANG - Erwandi, Antonius (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Management of Village-Owned Enterprises (BUMDes) as an effort by the village government to increase Village Original Income through independent businesses with capital participation sourced from village original income. The results of the study indicate that BUMDes management is carried out by forming a management structure that aims to organize administration and regulate business management. Community participation in BUMDes is by being directly involved as clean water customers and being willing to pay monthly fees that are used for maintenance costs and capital for other business developments. The conclusion of the study is that BUMDes management is carried out in accordance with management guidelines through the formation of a management structure that is responsible to the village government as a capital provider in BUMDes businesses. Community participation in the utilization of BUMDes is directly involved in maintaining BUMDes assets and businesses. Suggestions Maintain the BUMDes management system that has been running so far and improve administrative management based on work performance. Increase community participation in various participations both directly and indirectly on the performance of village administrators and governments.